Dangding Magatru Batur-Batur Nu Suluk Karya Haji Hasan Mustapa (Suatu Analisa Tasawuf) - Siti Rahma Sahidah; Muliadi Muliadi; Cucu Setiawan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Literature is created by the urge that comes inside to reveal things. A writer can be referred to as a philosopher and psychiatrist who is able to express various problems not academically but through literary works. A wide variety of literary works continue to develop in Indonesia. But there are also literary works that are less known by today's society such as dangding which is one of sundanese literary works. The object of this research is the dangding of Magatru Batur- Batur Nu Suluk by Haji Hasan Mustapa. This study aims to analyze the literary work in the context of Sufism. This research model is qualitative with a type of library research. The research method used is content analysis. The results of this study show that Haji Hasan Mustapa is a salik with a pattern of Sufism falsafi teachings that expresses his spiritual experience through a literary work. In his work, he mentions that suluk is a method to draw closer to God through the guidance of a teacher, armed with knowledge, and not to leave the life of the world. In this paper also mentioned some advice for salik to always practice berfakur, know the purpose, noble character, and wisely respond to the worldliness. This study concluded that dangding Magatru Batur-Batur Nu Suluk is a sundanese literary work of high value, has a very deep sufistic meaning, and remains relevant to be read as spiritual advice in living modern life today. The author recommends that a broader study of Sufism and other aspects of the literary work be conducted.